2024
DOI: 10.7759/cureus.56013
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Efficacy of Physiotherapy Strategies in Alleviating Low Back Pain: A Comprehensive Review of Interventions and Outcomes

Priya Tikhile,
Deepali S Patil

Abstract: Low back pain (LBP) presents a significant burden globally, affecting individuals of all ages, but it is more common in adults aged 30-60 years old and demographics including race, ethnicity, and socioeconomic status. Physiotherapy interventions are commonly employed to manage LBP due to their non-invasive nature and potential for addressing underlying biomechanical dysfunctions. This comprehensive review aims to evaluate the efficacy of various physiotherapy strategies in alleviating LBP, considering a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Physiotherapy treatments are usually considered the first line of treatment for sciatica patients [3]. Physiotherapists usually prefer to treat LBP with sciatica using various exercises and electrotherapy treatments [4]. In recent studies, neurodynamic mobilization of the sciatic nerve showed good results in reducing the symptoms, whereas conventional treatments that include various exercises and also considered by many to date showed good improvements in patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…Physiotherapy treatments are usually considered the first line of treatment for sciatica patients [3]. Physiotherapists usually prefer to treat LBP with sciatica using various exercises and electrotherapy treatments [4]. In recent studies, neurodynamic mobilization of the sciatic nerve showed good results in reducing the symptoms, whereas conventional treatments that include various exercises and also considered by many to date showed good improvements in patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic primary LBP is defined by the World Health Organization as persistent or recurrent pain lasting more than three months without a clear underlying disease process, structural lesion, or deformity. Chronic low back pain (CLBP) predominates, affecting approximately one in six adults globally but can often be effectively managed without surgery in primary and community care settings [2]. Pain stemming from the lumbar, lumbosacral, or sacroiliac regions varies depending on the affected area.…”
Section: Introductionmentioning
confidence: 99%